Career Paths of Public Health Medicine Specialists in South Africa - Zweigenthal, Virginia E. M.; Pick, William M.; London, Leslie (Frontiers in Public Health, 2019)
Public health (PH) skills are core to building responsive and appropriate health systems, and PH personnel including medical specialists, are embedded in many countries’ health systems. In South Africa, the medical specialty in PH, Public Health Medicine (PHM), has existed for over 40 years. Four years of accredited training plus success in a single national exit exam allows specialist registration with the Health Professions Council of South Africa (HPCSA). However, there are few posts designated specifically for PHM specialists in SA’s health system. In view of uncertain roles, this research was designed to determine specialists’ career paths, their work, job satisfaction and perspectives on the future of the specialty. We combined three databases to generate the study population and invited all specialists to participate in an online or hard-copy survey. We found that in 2010, PHM was a small specialty of less 200 physicians. Of the 151 contactable, eligible physicians, 55.6% completed the questionnaire. Participants represented an ageing group (median age=49) of specialists and recent graduates were increasingly women. They largely worked in academic institutions (as managers, teachers and researchers) and in the public sector health system; were motivated by a sense of social justice and their training was formative, exposing them to work settings which they later entered; were largely highly satisfied at work, but many worked in non-specialist positions. Indeed, one fifth had not registered with the HPCSA as specialists. They were concerned about the specialty’s poor visibility and identity, but did not see other PH professionals as a threat. They believed that the specialty should refine its competencies, demonstrate its value and advocate for service positions at all levels of the public sector health service. PHM has a contribution to make – reorienting services to protect communities, preventing ill health, analysing disease burdens locally, identifying innovations in a resource-constrained health service, largely preoccupied with curative care services.